Developing outdoor spaces for work and study—an explorative place-making process - Jansson, Märit; Mårtensson, Fredrika; Vogel, Nina (Frontiers in Sustainable Cities, 2024)
Development of outdoor spaces for work and study is part of a larger transition towards sustainable communities, which can take advantage of more flexible ways of organising everyday life. Governance processes supported by physical spatial changes have the potential to bring together various actors and experts for local development. The aim of this study was to explore the possibilities of developing outdoor spaces for work and study in a collaborative process involving an upper secondary school, a local government administration, local businesses and research. The process took place in a South-Swedish small town and included developing outdoor areas for tasks traditionally carried out indoors, participatory workshops and meetings followed up through questionnaires and interviews. Overall, the introduction of outdoor places was positively evaluated, but engagement varied across actors and over time, and a number of obstacles and challenges in the process were pointed out. The study showed how vital it is to anchor ideas for place-making locally and having key persons in leading positions with time set-off to support the process. It also indicates how decisive spatial changes can be and how important it is that any physical intervention becomes an integrated part of a wider local process in order to make an imprint on local life and pedagogical practice.